ANALISIS MANAJEMEN RANTAI PASOK PADA UMKM KERUPUK IKANDESA BOJONG SARI (Journal Edutama Multidisciplinary Indonesian, 2024)
This study aims to analyze supply chain management in fish crackers MSMEs located in Gang Arpen, Bojong Sari Village, Kedungwaringin District. This MSME processes fish into crackers and has an important role in the local economy. The research uses a qualitative approach with a case study method, which relies on in-depth interviews and direct observation to collect data from MSME owners, raw material (fish) suppliers, as well as retailers and distributors involved in the supply chain. The results showed that procurement of fish raw materials is done through local suppliers, but quality and stability of supply are often the main constraints. The production process is manual and inefficient, although production capacity can still be increased with modern technology. Product distribution is generally limited to local markets and traditional retailers, which limits market expansion. Other constraints include sub-optimal stock management and limited distribution. Based on these findings, it is recommended that MSMEs improve supply chain management by implementing a more integrated system, improving the quality of raw material supply, and expanding distribution channels, including through digital platforms. Improving production and distribution efficiency can help fish crackers MSMEs expand their market and improve competitiveness in local and global markets.